Case Report: Circulating Tumor DNA Fraction Analysis Using Ultra-Low-Pass Whole-Genome Sequencing Correlates Response to Chemoradiation and Recurrence in Stage IV Small-Cell Carcinoma of the Cervix - A Longitudinal Study - Abbas, Ata; Gruner, Morgan; Karohl, Jennifer; Rose, Peter G.; Joehlin-Price, Amy; Stover, Daniel; Mahdi, Haider (Frontiers in Oncology, 2021)
Neuroendocrine carcinoma of the cervix is a rare and aggressive form of cervical cancer that presents with frequent metastasis at diagnosis and high recurrence rates. Primary treatment is multimodal, which often includes chemotherapy with or without radiation therapy. There is no data available to guide treatment for recurrence, and second-line therapies are extrapolated from small cell lung carcinoma data. Close monitoring of these patients for recurrence is paramount. Evaluation of circulating tumor DNA (ctDNA) in the peripheral blood is an attractive approach due to its noninvasive nature. Ultra-low pass whole genome sequencing (ULP-WGS) can assess tumor burden, response to therapy, and predict recurrence; however, data are lacking regarding the role of ULP-WGS in small cell carcinoma of the cervix. This study demonstrates a patient whose response to chemotherapy and cancer recurrence was accurately monitored by ctDNA analysis using ULP-WGS and confirmed with radiologic imaging findings.